Shared and unique common genetic determinants between pediatric and adult celiac disease. Issue 1 (December 2016) - Senapati, Sabyasachi; Sood, Ajit; Midha, Vandana; Sood, Neena; Sharma, Suresh; Kumar, Lalit; Thelma, B.
Abstract Background Based on age of presentation, celiac disease (CD) is categorised as pediatric CD and adult CD. It however remains unclear if these are genetically and/or phenotypically distinct disorders or just different spectrum of the same disease. We therefore explored the common genetic components underlying pediatric and adult CD in a well characterized north Indian cohort. Methods A retrospective analysis of children (n  = 531) and adult (n  = 871) patients with CD between January 2001 and December 2010 was done. The database included basic demographic characteristics, clinical presentations, associated diseases and complications, if any. The genotype dataset was acquired for children (n  = 217) and adult CD patients (n  = 340) and controls (n  = 736) using Immunochip. Association analysis was performed using logistic regression model to identify susceptibility genetic variants. Results The predominant form of CD was classical CD in both pediatric and adult CD groups. There was remarkable similarity between pediatric and adult CD except for quantitative differences between the two groups such as female preponderance, non-classical presentation, co-occurrence of other autoimmune diseases being more common amongst adult CD. Notably, same HLA-DQ2 and –DQ8 haplotypes were established as the major risk factors in both types of CD. In addition, a few suggestively associated (p  < 5 × 10−4 ) non-HLA markers were identified of which onlyANK3 (rs4948256-A; rs10994257-T) was found to be shared and explain risk for ~45 % of CD patients with HLA allele. Discussion Overall phenotypic similarity between pediatric and adult CD groups can be explained by contribution of same HLA risk alleles. Different non-HLA genes/loci with minor risk seem to play crucial role in disease onset and extra intestinal manifestation of CD. None of the non-HLA risk variants reached genome-wide significance, however most of them were shown to have functional implication to disease pathogenesis. Functional relevance of our findings needs to be investigated to address clinical heterogeneity of CD. Conclusions This present study is the first comparative study based on common genetic markers to suggest that CD in pediatric age group and in adults are the spectrum of the same disease with novel and shared genetic risk determinants. Follow-up fine mapping studies with larger study cohorts are warranted for further genetic investigation.